Responding To Literary Texts Through Poetry Writing - Jerome, Collin (Centre for Language Studies, 2012)
There are various ways in which readers respond to literature. This article discusses how readers (students in particular) can express their ideas and thoughts about the literary texts they have read through poetry writing. It begins with an overview of reader response theory and the field of literary response research, followed by a discussion of oral and written forms of readers’ responses to literature and a classroom activity that requires students to express their thoughts about literary characters in poetic forms. The article also highlights students’ proficiency, and literacy and literary skills as some of the factors that need to be considered when using poetry writing as a way of responding to literature.